Massless representation of massive superfields and tree amplitudes with the pure spinor formalism - Sitender Pratap Kashyap; Carlos R. Mafra; Mritunjay Verma; Luis Ypanaqué (Journal of High Energy Physics, 2025)
Abstract We construct the unintegrated vertex operator at the first mass level of the open superstring from the OPE of massless vertices. Using BRST cohomology manipulations, the tree amplitude of two massless and one massive state is rewritten in terms of the pure spinor superspace kinematic expression of the massless four-point amplitude at the α ′ 2 level. A generalization relating the partial n-point tree amplitudes with one massive state and linear combinations of the α ′ 2 corrections to n+1 massless amplitudes is found and shown to be consistent with unitarity.